Logico-Semantic Relation of Clause Complexes in Figurative Languages in The Devil Wears Prada Film - Dini Riandini (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
The research aimed to determine types of logico-semantic relation of clause complexes in figurative languages and how The Devil Wears Prada film's logic-semantic realization. This study's data consisted of logico-semantic relation of complex clauses observed in the figurative languages in its film. This study took a qualitative method. There were 30 clause complexes in figurative languages as the sample. According to the analysis, the researcher found that logico-semantic relation types of clause complexes in the figurative languages were expansion and projection. There were 30 logico-semantic relations or 100% of the entire number of logico-semantic relations, with 28 items or 94% of expansion and 2 items or 6% of projection. In the case of expansion, it involved elaboration, extension, and enhancement, whereas projection comprised the projection. The locution projection is not employed at all. The expansion (elaboration) becomes the dominating sort of logico-semantic relation employed in the text, occurring 13 times (46%). Then, expansion (extension) happens 10 times or 34%, while expansion (enhancement) occurs 3 times or 10%. Furthermore, the projection (idea) appears twice, for a total of 7%. The last logico-semantic relation is projection (locution), which has no proportion (0 times or 0.00%).